ADVERSITY SKILLS IN YOUNG FAMILY TOBELO TRIBE IN GAMSUNGI VILLAGE - HALMAHERA UTARA - Pujiyanti, Arifah (Departemen Psikologi Pendidikan dan Bimbingan FIP Universitas Pendidikan Indonesia, 2020)
Adversity skills are the ability to respond to adversity and a series of ways to improve response to adversity. This study aims to produce profiles of adversity skills in married couples (husband and wife) in young families (aged 1-5 years) Tobelo tribe in responding to family problems. The data was collected using the Quick Take ARP (Adversity Response Profile) scale adopted from Paul G. Stolz, and involved research respondents of thirty married couples. Descriptive data analysis using one way ANOVA. The results showed that the profile of adversity skills in young Tobelo tribal families was in the campers category on average. That is, the average young family is still in the comfort zone and requires an effort trigger to be more successful in the family. The implications of these findings are used as data on the initial conditions of adversity skills, which can then be followed up to conduct further research by developing instruments used to uncover urgent family problems.